[tex]A=(-2,1),\ B=(1,-5),\ C=(4,1),\ D=(1,3)\\Bedziemy\ korzystali\ ze\ wzoru:\\|AB|=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\|AB|=\sqrt{(1+2)^2+(-5-1)^2}=\sqrt{3^2+(-6)^2}=\\=\sqrt{9+36}=\sqrt{45}[j][/tex]
[tex]|BC|=\sqrt{(4-1)^2+(1+5)^2}=\sqrt{3^2+6^2}=\\=\sqrt{9+36}=\sqrt{45}[j][/tex]
[tex]|CD|=\sqrt{(1-4)^2+(3-1)^2}=\sqrt{(-3)^2+2^2}=\\=\sqrt{9+4}=\sqrt{13}[j][/tex]
[tex]|AD|=\sqrt{(-2-1)^2+(1-3)^2}=\sqrt{(-3)^2+(-2)^2}=\\=\sqrt{9+4}=\sqrt{13}[j][/tex]
[tex]Obw=|AB|+|BC|+|CD|+|AD|\\Obw=\sqrt{45}+\sqrt{45}+\sqrt{13}+\sqrt{13}\\Obw=2\sqrt{13}+2\sqrt{45}[j][/tex]